The Relevance of Cognitive Behavioral Models of Post-Traumatic Stress Following Child Maltreatment: A Systematic Review. (January 2021) - Wiseman, Hannah; Hamilton-Giachritsis, Catherine; Hiller, Rachel M.
While it is known that young people exposed to maltreatment or abuse are at elevated risk of developing post-traumatic stress disorder (PTSD), much of our current knowledge of mechanisms that link trauma to childhood PTSD is based on single-incident, often noninterpersonal, trauma. Theoretical models highlight psychological processes of appraisals, memory, and coping as important for the development of PTSD. The aim of this review was to synthesize the literature on the role of these key psychological processes in relation to PTSD in maltreated children and teens. Studies were included if they (1) identified a sample of maltreated individuals, ≤18 years old; (2) measured (a) trauma memory, (b) appraisals, or (c) post-trauma cognitive or behavioral responses; and (3) measured PTSD symptoms. The systematic search of three electronic databases (American Psychological Association PsychNet, PubMed, and Published International Literature on Traumatic Stress) resulted in the inclusion of 36 papers, which described 31 studies and 33 unique samples. The review found cognitive behavioral models of PTSD appeared appropriate for understanding outcomes following maltreatment, but further research is needed on all processes, particularly trauma memory. Overall, there remain significant gaps in our knowledge of how psychological processes link maltreatment to PTSD. There is limited evidence concerning how maltreatment-related characteristics (e.g., chronicity, duration, and type of abuse) influence psychological processes and in turn affect outcomes. This review recommends further research in this area and suggests that, at the very least, comprehensive assessment should be conducted with all young people reporting maltreatment to identify appraisals and coping strategies that will potentially impact on their ongoing adjustment.